Analysis of the level of CO parameter air pollution on the road of Makassar City - Saleh, Rahmatiah; Susilawaty, Andi; Ibrahim, Irviani (Public Health Science & Religion, 2023)
Background: Air pollution comes from gas emissions from motor vehicle combustion, human daily activities, or from industrial and residential activities. Transportation routes in the form of roads that are dense with motorized vehicles are places with a high level of pollution. Gas emissions from vehicles that come from combustion in the engine does not burn completely to produce carbon monoxide gas. Carbon monoxide gas is one of the most dangerous pollutants for health. Air Pollution Level CO parameters on Jalan AP Pettarani Makassar City were measured to assess the impact of exposure to carbon monoxide. Methods. The type of research used is an observational quantitative analytic study with a cross sectional approach. The population in this study was all ambient air on Jalan AP. Pettarani with a sample of 378 samples from 6 points 3 measurements, morning, afternoon, evening, for 7 days of the study. Results. The results of the Pearson Correlation test obtained -value of 0.000 (<0.05) indicating that there is a significant relationship between CO and Air Pollution Levels (ISPU). The correlation coefficient for Morning Co is r=0.980, Afternoon CO r=0.985 and Afternoon CO r=0.993 which shows a very strong relationship and a positive direction. Conclusion. For further researchers, it can be added with other parameter measurements and in data collection more attention to wind, temperature, humidity, and number of vehicles in air quality measurements.